Real‐world data on lenalidomide dosing and outcomes in patients newly diagnosed with multiple myeloma: Results from the Canadian Myeloma Research Group Database. (26th September 2022) - Mian, Hira; LeBlanc, Richard; Louzada, Martha; Masih‐Khan, Esther; McCurdy, Arleigh; Venner, Christopher P.; Stakiw, Julie; Kardjadj, Moustafa; Jimenez‐Zepeda, Victor H.; Sebag, Michael; White, Darrell; Aslam, Muhammad; et al.
Abstract: Using the Canadian Myeloma Research Group Database, a retrospective study of 167 newly diagnosed, transplant‐ineligible patients with multiple myeloma (MM) that received lenalidomide‐dexamethasone as front‐line treatment was conducted to understand the impact of lenalidomide dosing. Starting dose modifications were common, 42% of patients started on lenalidomide <25 mg with normal renal function. During treatment course, 35% of patients required further dose reduction. Dose reductions in the first year did not have an impact on progression free survival or overall survival. Further studies need to be conducted to understand the impact of dosing strategies of anti‐MM agents in the real world.